2006
DOI: 10.2353/ajpath.2006.060049
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Mediated Transforming Growth Factor-β Activation Regulates Homeostasis of the Pulmonary Epithelial-Mesenchymal Trophic Unit

Abstract: Trophic interactions between pulmonary epithelial and mesenchymal cell types, known as the epithelialmesenchymal trophic unit (EMTU), are crucial in lung development and lung disease. Transforming growth factor (TGF)-␤ is a key factor in mediating these interactions, but it is expressed in a latent form that requires activation to be functional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 48 publications
1
80
0
Order By: Relevance
“…Antibodies to involucrin and keratin 6 stained the superficial and suprabasal cells of the squamous metaplastic epithelium ( Figure 3R). A pattern of immunoreactivity similar to that seen in SM of the airways in COPD was seen in the squamous mucosa of the cervix, and in the epidermis at the edge of healing wounds (Supplemental Data and Supplemental (10). Indeed, we found that α v β 8 integrin expression ( Figure 4, A and B) and α v β 8 integrin-mediated TGF-β activation ( Figure 4C) in human airway fibroblasts was increased by treatment either with recombinant IL-1β (data not shown) or by coculture with squamous metaplastic (P3) epithelial cells.…”
Section: Sm In the Small Airways Of Copd Patients Involucrin Is A Comentioning
confidence: 73%
See 4 more Smart Citations
“…Antibodies to involucrin and keratin 6 stained the superficial and suprabasal cells of the squamous metaplastic epithelium ( Figure 3R). A pattern of immunoreactivity similar to that seen in SM of the airways in COPD was seen in the squamous mucosa of the cervix, and in the epidermis at the edge of healing wounds (Supplemental Data and Supplemental (10). Indeed, we found that α v β 8 integrin expression ( Figure 4, A and B) and α v β 8 integrin-mediated TGF-β activation ( Figure 4C) in human airway fibroblasts was increased by treatment either with recombinant IL-1β (data not shown) or by coculture with squamous metaplastic (P3) epithelial cells.…”
Section: Sm In the Small Airways Of Copd Patients Involucrin Is A Comentioning
confidence: 73%
“…Neutralizing anti-β8 and β8 siRNA blocked only approximately 50% of the total TGF-β activation as determined using a TGF-β neutralizing antibody that inhibits the function of all 3 TGF-β isoforms ( Figure 5C). Thus, the incomplete inhibition of TGF-β activation could be due to activation of TGF-β2 by an α v β 8 -independent mechanism, since α v β 8 is only involved in the activation of TGF-β1 and -β3 (10,20). Alternatively, the incomplete inhibition may be due to the relatively poor efficacy of the β8-neutralizing antibody and the incomplete silencing achieved with β8 siRNA ( Figure 5A).…”
Section: Sm In the Small Airways Of Copd Patients Involucrin Is A Comentioning
confidence: 99%
See 3 more Smart Citations